Tanggung Jawab Notaris Terhadap Pembatalan Akta Atas Terjadinya Tindakan Pemalsuan Oleh Notaris - Munib, Ali; Suratman, Suratman; Isnaeni, Diyan (JURNAL USM LAW REVIEW, 2024)
The aim of this research is to analyze the form of the notary's responsibility for deeds that are canceled due to forgery by the notary and to find out legal certainty regarding deeds that are canceled due to forgery by the notary. Notaries as public officials have a very important role in issuing authentic deeds as specified in statutory regulations. Their role does not rule out the possibility of misuse of the notary's authority over the deed issued. The involvement of a notary or even being the main actor in committing the crime of falsifying an authentic deed is very detrimental to the parties or parties involved. For this reason, notaries must be responsible for violations of the law. This research uses a statutory approach (statute perspective) and a conceptual approach. The method for collecting legal materials is a qualitative descriptive literature study. The results of the first research explain in detail the form of notary responsibility for forged deeds, legal sanctions will also be received by the notary if they are proven to have forged documents. These sanctions are in the form of administrative sanctions or codes of ethics, civil sanctions, and even criminal sanctions. This is as stated in Law Number 12 of 2014, an amendment to Law Number 30 of 2004 concerning Notary Positions, the Civil Code, and the Criminal Code. The results of the second research show that legal certainty regarding Notarial deeds will be reduced if the Notarial deed contains forgeries or is not in accordance with the legal events that occurred. If this happens, the authentic deed will be degraded and even declared null and void. The novelty in this research is that the object studied focuses on the Notary's responsibility for deeds that are canceled due to elements of forgery committed by the Notary and explains them one by one. Tujuan dari penelitian ini yaitu untuk menganalisis bentuk tanggung jawab Notaris terhadap akta yang dibatalkan sebab adanya pemalsuan oleh Notaris dan mengetahui kepastian hukum terhadap akta yang dibatalkan sebab adanya pemalsuan oleh Notaris. Notaris sebagai pejabat umum memiliki peran yang sangat penting dalam penerbitan akta autentik sebagaimana yang telah ditentukan dalam peraturan perundang-undangan.. Keterbilatan Notaris atau bahkan menjadi aktor utama dalam melakukan tindak pidana pemalsuan akta autentik sangatlah merugikan bagi para pihak atau penghadap. Dari sebab itulah Notaris harus bertanggung jawab atas pelanggaran hukum yang dilakukan. Penelitian ini menggunakan pendekatan perundang-undangan dan pendekatan konsep. Metode pengumpulan bahan hukum adalah studi kepustakaan deskriptif kualitatif. Hasil penelitian pertama, menjelaskan secara rinci bentuk tanggung jawab Notaris terhadap akta yang dipalsukan, sanksi hukum juga akan diterima oleh Notaris jika terbukti telah melakukan pemalsuan surat. Sanksi-sanksi tersebut berupa sanksi administratif atau kode etik, sanksi perdata dan bahkan sanksi pidana. Hal ini sebagaimana telah dinyatakan dalam Undang-undang Nomor 12 Tahun 2014 perubahan dari Undang-undang Nomor 30 Tahun 2004 tentang Jabatan Notaris, Kitab Undang-undangn Hukum Perdata dan Kitab Undang-undang Hukum Pidana. Hasil penelitian kedua menunjukkan bahwa kepastian hukum terhadap akta Notaris akan berkurang jika akta Notaris berisikan pemalsuan atau tidak sesuai dengan peristiwa hukum yang terjadi. Jika ini terjadi, akta autentik akan didegradasi dan bahkan dinyatakan batal demi hukum. Kebaruan dalam penelitian ini adalah objek yang diteliti fokus pada tanggung jawab Notaris terhadap akta yang dibatalkan sebab adanya unsur pemalsuan yang dikakukan oleh Notaris dan menguraikannya satu persatu.